Renal revascularization - Sanguinetti, J.; Altieri, C. E.; Bonilla, C.; Knobel, J. (Cirugía del Uruguay, 1971)
A five centime.tre sector of the splenic artery was implanted in a tunnel of the renal parenchima after reduction of arterial renal flow through progressive clamping of the renal artery. Results were studied by means of renal arteriography and scintillography. A descent of arterial pressure -which had increased as a consequence of previous ischemia was also observed.